Co-creation applied to the management of innovation in sectors of a local economy - Hernández-Gil, Cristian; Herrera-Peralta, Cristian Camilo (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Co-creation in educational settings has become a new way of generating skills based on the acquisition of learning from proposing solutions to the dynamics of the productive sector. The objective of this research was to apply the co-creative method to sectoral problems of the local economy of a municipality in the amazonia colombiana region based on collaboration and the shared construction of knowledge between university students and entrepreneurs. For this, a study with a qualitative approach and participatory action research was designed based on the methodology of design thinking or design thinking using techniques such as interviews and observation. The results bet on proposing solutions to make adjustments to business management situations in the sectors analyzed, associated with user service, the development of new products, and the reinduction of human talent.